Multinational Enterprises, Sustainability Activities, and Implementation of Sustainable Development Goals in Africa - Afriyie, Edmund Osei; Zahoor, Nadia (Palgrave Macmillan, 2023)
Multinational enterprises (MNEs) are expected to address socioeconomic challenges in host and home countries as they are key drivers of change in addressing the United Nations’ sustainable development goals (SDGs). However, MNEs in sub-Saharan Africa—part of the global south—have seen a slow engagement in adopting and promoting SDGs. This chapter identifies the role of MNEs in the implementation of SDGs. This chapter further explores how MNEs frame their sustainability efforts toward local development and the roles governments play in promoting corporate sustainability. The key contribution of this chapter is to highlight sustainability activities, SDG targets, and organizational activities aimed at addressing SDGs.
Keywords: Multinational enterprise; Sustainable development goals; Sub-Saharan Africa; SDGs